Influence of Hydroxyethyl Cellulose Treatment on the Mechanical Properties of Jute Fibres, Yarns, and Composites. (24th October 2013) - Nag, Ranajit K.; Long, Andrew C.; Clifford, Michael J.
Abstract : Jute yarns were treated by tap water with and without tension at room temperature for 20 minutes and then dried. Fibre and yarn strength were measured before and after treatment. Unidirectional (UD) composites were made by both treated and untreated yarns with and without applying hydroxyethyl cellulose (HEC) as size material. Water-treated jute yarns without tension and composites made of those yarns showed decreased strength, and water treated jute yarns with tension and composites made of those yarns showed increased strength with respect to raw yarns and composites made of raw yarns. However, no specific trend was noticed for fibre tensile strength and tensile modulus. HEC sized yarns showed up to 12% higher failure load with respect to unsized yarns, and composites made of HEC sized yarns showed up to 17% and 12% increase in tensile strength and tensile modulus, respectively, compared to composites made of similar types of unsized yarns.